(untitled) (Ricos Biology, 2025)
The global prevalence of diabetes mellitus has necessitated the exploration of innovative therapeutic strategies that enhance patient compliance and optimize glycemic control. Conventional insulin therapy, though effective, often poses challenges due to invasive administration, fluctuating absorption, and limited patient adherence. The development of a glucose-responsive swallowable insulin system represents a transformative advancement in diabetes care. This approach integrates polymeric nanocarriers and bioengineered peptides that respond dynamically to blood glucose fluctuations, releasing insulin in a controlled and physiological manner. Polymeric micelles, hydrogels, and phenylboronic acid-modified nanocarriers have shown remarkable glucose sensitivity, making them potential candidates for oral formulations. These systems are designed to remain stable in the gastrointestinal environment while releasing insulin upon sensing hyperglycemia. The incorporation of glucose oxidase-based feedback mechanisms further enhances precision by coupling enzymatic sensing with insulin release kinetics. This manuscript critically reviews molecular design strategies, in vitro and in vivo results, and translational challenges in developing glucose-responsive swallowable insulin. Statistical models were applied to evaluate the relationship between glucose concentration and insulin release kinetics, revealing a high degree of correlation (R² > 0.95) between predicted and observed values. The findings underscore the promise of swallowable insulin as a non-invasive, self-regulating, and patient-centered therapeutic alternative. Future studies should emphasize large-scale clinical validation, long-term stability, and integration with digital glucose monitoring platforms to ensure real-world applicability